PTH-350 The effect of mucinous pathology on outcomes in rectal cancer. (22nd June 2015) - Shamji, T; Jones, H; Harris, D
Abstract : Introduction: Mucinous adenocarcinoma (MA) is a specific morphological subtype of colorectal cancer (CRC). It is characterised when >50% of the tumour is composed of extracellular mucin pools. This subtype represents 5–15% of CRC. There have been several studies demonstrating poor overall survival in mucinous CRC, in our study; we aim to assess the impact of mucinous pathology in rectal cancers. Method: A total of 291 patients with rectal cancer were identified and studied between 2002–2013 in a tertiary colorectal centre (Swansea Colorectal Unit, Swansea, UK). A prospectively maintained central pathology database was used to identify patients with rectal cancer. The histopathological report was used to identify the tumour as either mucinous or non-mucinous (NMA). The primary outcome measures were disease free survival (DFS) and overall survival (OS) in patients that received surgery alone. Results: There were 26 patients with MA and 265 NMA. There was no significant difference in median age and sex between both groups. The most common surgical procedure performed was an anterior resection in both groups (MA (58%) and NMA (65%). Poor differentiated tumours were found in 35 and 12% of MA and NMA, respectively (p = 0.001). There was no difference in DFS (p = 0.503) or OS (p = 0.478) in the 60 month follow-up period. Conclusion: Our study did not demonstrate a significant difference in survival outcomes in patients with mucinous rectal cancer compared to NMA. However, the study did find a significant difference in tumour differentiation with MA associated with poor differentiated tumours. Disclosure of interest: None Declared.